EDUKASI TENTANG PENYAKIT DIABETES MELITUS: EDUCATION ABOUT DIABETES MELLITUS - Yestiani Norita Joni; Muhammad Kaisar (Sekolah Tinggi Ilmu Kesehatan Kesetiakawanan Sosial Indonesia, 2021)
One indicator of the quality of health both at the level of understanding and the source of information provided. Likewise with people with diabetes, it is necessary to provide information and education related to proper management of their disease conditions. With diabetes knowledge, it is hoped that it will be in line with the diabetes compliance in complying with the treatment program. The objectives of this activity include: 1) Providing motivation to partner communities in increasing awareness of people with diabetes in particular, 2) The ability and success of the community in supporting family participation in caring for and treating family members, 3) Ability to prevent diabetes complications in accordance with the Standards existing health services and carried out in a sustainable manner. The number of successful participants was recorded based on a list of 20 people. This activity was carried out boldly using a zoom meeting because it was prepared in order to prevent the spread of the COVID-19 virus.